(untitled) (Canadian Journal of Native Studies, 2026)
The Ontario Ministry of Education’s (OME) Implementation Plan: Ontario First Nation, Métis, and Inuit Education Policy Framework (2014) restates its commitment to the principles of the 2007 Policy Framework. This analysis examines the value orientations and assumptions couched in the rhetoric of the 2014 Implementation Plan. The paper first situates Indigenous education in a contemporary context, and subsequently discusses the implications of the respective discourses as they are framed in the Implementation Plan document. The intent is to provide Indigenous and non-Indigenous students, communities, Indigenous education councils, administrators, teachers and other stakeholders with critical considerations of the OME Indigenous education policy initiatives.